Strategies for the implementation of best practice guidelines in operating theatres: An integrative literature review - Olukemi O. Owolabi; Portia J. Jordan; Margaret Williams; Wilma ten Ham-Baloyi (AOSIS, 2021)
Best practice guidelines (BPGs) exist for operating theatre (OT), but strategies to implement them are lacking. To address the gap, an integrative review was undertaken to identify strategies which can be used to implement BPGs in OT. This article aimed to summarise the best existing literature in order to identify and describe strategies for the implementation of BPGs in OT. An extensive search was undertaken to include relevant literature from February 2005 to March 2020 using the following databases: CINAHL, Medline, Biomed Central, Academic Search Complete and Health Source: Nursing/Academic Edition (EBSCOhost) and the Cochrane library. This integrative literature review followed the methodology proposed by Whittemore and Knafl, namely: (1) identification of the research problem, (2) search of the literature, (3) evaluation of the data, (4) analysis of the data and (5) presentation of the results. On completion of the critical appraisal, 15 (n = 15) articles met the inclusion criteria and relevant data were synthesised. The review identified six strategies facilitating implementation of BPGs in OT, namely, communication, education materials and mass media, academic detailing, opinion leaders, audit and feedback, and teamwork and collaboration. The review validated strategies for the implementation of BPGs in OT. Implementation of BPGs is essential to both provide and improve patient care and to benefit health outcomes. This review is expected to contribute to the provision of strategies to implement BPGs in OT.